Varibaculum timonense sp. nov., a new bacterial species isolated from human stool sample - Lo, C.I. (New Microbes New Infect, 2019)
Varibaculum timonense sp. nov. strain Marseille-P3369(T) (= CSURP3369) is a new species from the order Actinomycetales that has been isolated from a fresh stool sample of a healthy French woman.